Design and development of sustainable manufacturing systems selected, peer reviewed papers from the Electronic and Green Materials International Conference (EGM 2015), the Engineering Technology International Conference (ET 2015), the Green Design and Manufacture International Conference (GDM 2015), July 31- August 1, 2015, Surabaya, Indonesia - Mohd Mustafa Al Bakri Abdullah; Rafiza Abd. Razak; Muhammad Mahyiddin Ramli; Shayfull Zamree Abd. Rahim; Rizalafande Che Ismail; Mohd. Nasir Mat Saad (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the Electronic and Green Materials International Conference (EGM 2015), the Engineering Technology International Conference (ET 2015), the Green Design and Manufacture International Conference (GDM 2015), July 31 - August 1, 2015, Surabaya, Indonesia.